Cladding effects on silica directional couplers - Ary Syahriar; Ahmad Husin Lubis; Jusman Syafii Jamal; Anwar Mujadin; Ahmad Juang Pratama (Universitas Ahmad Dahlan, 2019)
Directional couplers are widely used as passive and active optical devices in fibre and integrated optics, and form the basis of components such as switches, modulators and wavelength filters. They consist of two closely-spaced parallel waveguides, whose separation is sufficiently small that power may be transferred between the modes propagating in the two guides through an interaction involving their evanescent fields. In this paper results are presented for a range of near infrared single mode silica directional couplers fabricated by electron beam irradiation. The effects of over cladding layers will be highlighted. Changes on coupling coefficient due to different cladding refractive indexes will also be examined. The coupled mode theory will be employed to fit the experimental results with prediction by theory. It is found that over cladding layer alters the transmission characteristics of silica directional couplers.